E-CityFarm: sustainable small-scale food production integrated fish and crop cultivation - R. Wahyu Tri Hartono; Sakinah Puspa Anggraeni; Fajri Habibie Suwanda; Eka Pratiwi; Regina Nur Shabrina; Vina Fitriana (Universitas Ahmad Dahlan, 2022)
E-CityFarm is an electronic system that can control the parameters needed to grow fish and plants integratedly. It can control temperature, water acidity, and utilizing the neural network method able to count the number and length of fishes also their weight. The weight will be directly proportional to the need for feed. In E-CityFarm, various variables are processed by multitasking, therefore real time operating system (RTOS) is used. RTOS has several advantages in terms of: concurrency, pre-emption, capacity, flash size, synchronization tools, third party software, and convenience. RTOS is real time where in the execution process it will work in parallel for all existing processes according to the time specified. E-CityFarm implements RTOS to improve and maintain the quality of system measurement accuracy, which is expected to help users maintain product quality. In several experiments, the measurement results still have deviations compared to conventional measurements, deviations in measurements for: temperature 0.46%, light intensity 1.935%, 4.93% (3 levels) and weight control 1.995% (98.005% accuracy). Within 14 months the growth of fish and plants seemed to be very controlled, fish and plants grew well, thus E-CityFarm is a feasible system to be developed in areas that have limited land and water.